STRENGTHENING LEADERSHIP CHARACTER THROUGH THE “CAPTAIN FOR A DAY” PROGRAM FOR ELEMENTARY SCHOOL STUDENTS - Khamim Wahyudi; Ana Andriani; Subuh Anggoro; Wakhudin (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Low student participation and the dominance of teacher-centered learning constitute the main background of this study, as they contribute to the underdevelopment of leadership among elementary school students. This condition indicates the need for experience-based learning strategies that provide opportunities for students to actively participate in classroom activities. The purpose of this study is to describe the implementation of the “Kapten Sehari” (Captain for a Day) Program in fostering leadership among elementary school students in the Gajah Mada Cluster, Cipari District, Cilacap Regency, to analyze the teacher’s role in guiding and facilitating the program implementation, and to examine its impact on the development of students’ leadership. This research employs a qualitative approach with a phenomenological design. The data consist of primary and secondary sources, including the school principal, fifth-grade teachers, and fifth-grade students involved in the program. Data collection techniques include observation, semi-structured interviews, and documentation. Data validity is ensured through source triangulation and technique triangulation. Data analysis follows the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing, and is further strengthened by thematic analysis. The findings reveal that the “Kapten Sehari” Program is implemented through a daily rotation system that provides all students with the opportunity to act as class leaders. The captain’s activities include leading prayers, organizing lines, taking attendance, and reminding classmates of their responsibilities. The implementation of the program provides direct learning experiences that enhance students’ courage, self-confidence, responsibility, independence, and social skills. The teacher’s role as a facilitator, mentor, and evaluator, along with the principal’s policy support, are key factors in the success of the program and in strengthening a character-based school culture